Analisis Partisipasi Pendidikan Tinggi di Indonesia - Ririn Andrian Ririn; Mike Triani (Universitas Negeri Padang, 2026)
This study aims to examine the factors influencing the Gross Enrollment Ratio (GER) in higher education in Indonesia, which remains relatively low and uneven across regions. The study utilizes panel data from 34 provinces over the 2020–2024 period, incorporating variables such as GRDP per capita, internet access, the open unemployment rate, and population growth rate. The analytical method employed is panel data regression using a random effect model, selected based on the chow, hausman, and lagrange multiplier tests. The results indicate that GRDP per capita has a negative and significant effect on GER. In contrast, internet access and the open unemployment rate have positive and significant effects, while population growth has a negative but insignificant effect. Collectively, all variables are found to have a significant influence on GER. These findings highlight the important roles of economic factors, digital access, labor market conditions, and population growth in shaping higher education participation, and provide a basis for formulating more effective policies to increase higher education participation in Indonesia.